Evaluation and validation of an ion mobility quadrupole time‐of‐flight mass spectrometry pesticide screening approach. Issue 10 (15th March 2018) - Bauer, Anna; Kuballa, Juergen; Rohn, Sascha; Jantzen, Eckard; Luetjohann, Jens
Abstract: An ion mobility quadrupole time‐of‐flight mass spectrometry‐based pesticide suspect screening methodology was developed and validated covering 20 plant‐derived food matrices deriving from six commodity groups of different complexity according to the actual European Commission document SANTE/11813/2017 applying a QuEChERS sample preparation protocol. The method combines ultra‐performance liquid chromatography, traveling wave ion mobility, and quadrupole time‐of‐flight mass spectrometry. Besides the determination of the physicochemical property collision cross‐section and the establishment of a corresponding scientific suspect screening database comprising 280 pesticides for several pesticides, different protomers, sodium adducts, as well as dimers were identified in ion mobility spectrometry traces. Additionally, collision cross‐section values were included in the validation requirements regarding chromatography and mass spectrometry for the detection of pesticides. A collision cross‐section value window was analyzed within a tolerable error of ±2%. For this cross‐matrix validation, screening detection limits were determined at concentration levels of 0.100 mg/kg (84% of the original pesticide scope), 0.010 mg/kg (56%), and 0.001 mg/kg (21%). By application of ion mobility spectrometry, the compound identification was improved due to independence of commodity of concern and concentration levels of analyte molecules, as false assignments are reduced by application of a collision cross‐section range.